Pheochromocytoma: reporting of two cases with a brief review - Patowary, BN; Kumar, S; Praveen, CR; Majhi, PC; Yadav, RK; Tayal, A; Chhetri, PK (Journal of College of Medical Sciences-Nepal, 2012)
Pheochromocytoma arise from the chromaffin cells of adrenal gland or cells of sympathetic ganglion. The tumors secrete excessive adrenaline and nor-adrenaline and may cause severe elevation of blood pressure. Cardinal symptoms of pheochromocytoms are headache, diaphoresis, palpitation and high blood pressure which may be paroxysmal in nature. However, 10% of pheochromocytomas are only incidentally discovered during investigation of the patient for other reasons not related to suprarenal disease. We have reported here two cases of suprarenal tumors (pheochromocytoma), one of which is incidentally found while investigating her chest and epigastric pains. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 78-86 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6817